Diretrizes para aplicação dos conceitos de sustentabilidade na reabilitação de edifícios em centros urbanos para fins de habitação popular : análise do programa morar no Centro-Vitória (ES) - Zamborlini-Waldetario, Kamila (2009)
The interventions for rehabilitation of underutilized urban areas have been set up as a new attitude toward the built environment, walking in the opposite direction of the urban centers emptying. In Brazil, owing to the time of formation of the cities and